INVITRO GLYCEMIC RESPONSE OF GLUTEN-FREE BISCUITS AND THEIR MAIN INGREDIENTS: A SYSTEMATIC REVIEW - MALINI H MADHAV,; DR. SHEBA SANGEETHA JEYARAJ, (The Bioscan, 2026)
Gluten-free (GF) biscuit uses different ingredients for substituting gluten-based ingredients which gives rise to varied glycemic index (GI) based on the nature of the ingredient. Invitro starch digestion is a non-invasive laboratory method to estimate starch digestion and GI. This study aimed at performing a systematic review on invitro starch digestion conducted in GF biscuits. The electronic search using PRISMA guidelines was conducted in PubMed, DOAJ and Google Scholar resulting in 18 eligible studies. All of the nine finally selected studies showed medium risk of bias evaluated using the QUIN tool. The number of studies that reported high GI were 1; medium–6 and low–2 in the experimental biscuits. All studies that reported starch hydrolysis revealed a higher dietary fibre or slowly digestible starch content. All selected studies reported improved nutritional profile, variable hardness and overall acceptability based on the choice and processing method of ingredients. This systematic review identified several gaps such as the need to study nature and processing techniques of ingredients, optimizing proportion of ingredients to improve palatability and consumer acceptability of biscuits. Further studies are required to understand the impact of several GF ingredients on the starch digestion and glycemic index of biscuits.